Sikap Remaja Putri Terhadap Pernikahan Dini di Dusun Wonontoro Desa Jatiayu Kecamatan Karangmojo Kabupaten GUnungkidul - Ekawati Ekawati; Kiki Indriyanti (Journal of Health (JoH), 2017)
Background: The phenomenon of early marriage among young people is already very widespread. Special Region of Yogyakarta Ministry of Religious Affairs in 2015 showed that the Gunung Kidul ranked first in early marriage as many as 184 people (0.37%). According on population and family planning agencies nationwide (BKKBN) in 2014 showed that the high rate of early marriage because of low eduation, economic needs, culture of young marriage and arranged marriage. The purpose to know about the overview of teenage attitudes against early marriage in Wonotoro hamlet, Jatiayu village, Karangmojo, Gunung kidul regency. Methods: Types of quantitative descriptive study, with a total population of 40 respondents. Sampling using total population. Collecting data using questionnaires and closed scales, the percentage univariat data analysis presented in frequency distribution. Results: The attitude of the young women in the Wonontoro, Jatiayu village shows that teenage girls who supports marriage as much as 45.5%, and that does not support early marriage as much as 57.5%. Conclusion: The attitude of teenage girl against early marriage in Wonotoro, Jatiayu Village, Karangmojo, Gunung Kidul shows that the majority of teenage girls do not support early marriage as much as 23 respondents (57,5%).